Strategi Pemerintah Daerah dalam Tinjauan Program Kota Tanpa Kumuh (Studi pada Kelurahan Gading Kasri, Kecamatan Klojen, Kota Malang) - Ulum, M. Chazienul; Anggraini, Dini Heksa (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
The problem of slum settlements is a big challenge for both central and local governments. To overcome this problem, the Directorate General of Human Settlements conducted national development through the City Without Slum (KOTAKU) program. KOTAKU is a program to manage slum settlements into habitable settlements through community-based infrastructure development. Kelurahan Gading Kasri of Malang City is one of the sub-districts chosen by the Malang City Government to implement the City Without Slums program. Strategies in handling the slum areas in Gading Kasri Village can be analyzed with the theory of types of strategies by Korten, which include organizational strategies, program strategies, resource support strategies, and institutional strategies.